P. Kulish's "Ukraine" and folk dumas: linguistic and poetic analysis - Dyadyshcheva-Rosovetska, Juliya (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article is devoted to the study of Panteleimon Kulish's search for a productive model of development of the new Ukrainian literary language and ways of its enrichment, in particular at the expense of the language of folklore as an inexhaustible source. A linguistic and poetic analysis of Panteleimon Kulish's large-scale work "Ukraine: From the Beginning of Ukraine to Khmelnytsky's Father" and its comparison with some elements of the linguopoetics of folk dumas of the classical repertoire are presented. The real problems that arise in P. Kulish’s creative work when he tries to achieve a harmonious combination of authentic folk thought words and expressions and stylized author's innovations are demonstrated. The article shows the difficulties in the artist's selection of colored ethnographically linguistic material needed to create a folklore duma's color. The shortcomings of combining the author's elements with fragments of real dumas within one work of art are revealed. This technique is compared with the approach of Taras Shevchenko, who turned to "stylization" or "improvisation" in the folk spirit (M. Kotsyubynska) and isolated the resulting structures structurally, putting in the mouths of certain characters - the Blind or the Witch. The fundamental difference in the approaches to verbal creativity is differentiated on the one hand by the bearer of the oral-poetic tradition, which is only within the possibilities of Ukrainian folklore, and on the other - by the artist of the XIX century - its user, who perceives the folklore tradition not "from within" but "from outside" and addresses the entire literary heritage - domestic and world, as well as folklore - his own and other peoples. The counterproductiveness of some authorial experiments of P. Kulish on dumas samples is illustrated. Their results cannot be considered satisfactory due to illogicality, low intellectual saturation or from an aesthetic point of view. A somewhat excessive exoticism of the author's innovations has been recorded, which attracts the reader's undue attention to them and distorts his perception of the artistic fabric of the poetic work. The question of the specifics of the experimental text of P. Kulish is formulated. What prevails here is the scientific reconstruction of lost fragments of true dumas, the restoration of time-destroyed parts of the national epic, or the demonstration of the author's creative ability to practice folklore improvisation in a work of art. Depending on the answers, a comprehensive assessment can be made.
Keywords: lingvofolkloristics, lingvopoetics, lingvostylistics, P. Kulish, duma, poetic language, folklore, literature.